The effectiveness of illustration in conveying the meaning of Usman Awang’s poems / Muhammad Amirudin Nazri - Nazri, Muhammad Amirudin (2015)
The purpose of this research is to examine how effective the used of illustration to portrays Usman Awang's poem. Illustration can be used to catches attention to certain information. Illustration is something that the person will look first before they read the text, in any information in regard with any text for example short stories, novel and story books for children. Illustration also is one of the best methods in conveying messages. The presence of illustration can be the supporting tools to illustrate the content ofthe text. A good book cover illustration can determine the general success ofthe book unless you are a well-known writer who does not even need an illustration on his/her book cover to be noticed and purchased. The poem's book which has the touch of conceptual illustration can produce a good book with high commercial value especially in Malaysia; very seldom we find a poem's book which is translated into illustration